Assessing trace elements in striped dolphins from the Strait of Gibraltar: Clues to link the bioaccumulation in the westernmost Mediterranean Sea area and nearest Atlantic Ocean. (March 2017) - Rojo-Nieto, Elisa; Fernández-Maldonado, Carolina
Abstract: Dolphins are considered sentinel species in the marine environment. The Strait of Gibraltar is the only passage between the Mediterranean Sea and the Atlantic Ocean, being the transitional region which connects these two basins and one of the most important routes of cetacean migration worldwide. In this work, eight trace elements (TE) were studied in 45 samples of liver, kidney and muscle, from 15 specimens stranded in this study area. The preliminary results show, among others, the patterns of distribution of the TE in the target organs studied, the influence of sex, length and developmental stage in these TE concentrations and the Se/Hg ratio. Subsequently, the results of TE concentrations in liver have being compared to previous data on S. coeruleoalba from the westernmost Mediterranean Sea and the nearest Atlantic Ocean. For some elements (e.g. for As), concentrations are similar to those obtained from Atlantic samples, despite in other cases (e.g. for Cd) results are lined up with those observed in Mediterranean studies. In addition, in the case of some TE (e.g. Se and Zn) the results are in the middle of those reported for both basins, reinforcing the idea of the Strait of Gibraltar being a transitional zone. Present study is the first research regarding this issue in this outstanding region, aiming to give insights of how this matchless area can help to link TE concentrations observed in these Atlantic and Mediterranean threatened species. Highlights: Stranded dolphins are good bioindicators showing great potential as monitoring tools. Trace elements were first measured in stranded dolphins in the Strait of Gibraltar. Trace elements are compared among target organs and correlated to biological parameters. First report of Se/Hg ratio in cetaceans from this relevant transitional region. This region can be considered a transitional area between Mediterranean and Atlantic basins.